Inputs for bridge painting decision support: a synthesis. Issue 2 (21st March 2018) - Ghahari, Seyed Ali; Ha, Paul (Young Joun); Chen, Sikai; Alinizzi, Majed; Agbelie, Bismark; Labi, Samuel
Abstract : A bridge paint schedule is a set of treatment types (overcoat, recoat, spot repair) and timings. Age-based or performance-based scheduling decisions for painting steel bridge superstructures are often made using expert opinion, continuation of historical practice or explicit optimisation. Optimisation is the preferred mechanism because it yields solutions that are not only data based but also objective and defensible. The information needed as inputs for optimising painting application decisions (long-term paint scheduling) includes the agency and user costs associated with painting projects and the long-term performance of bridge paint coats or the painted steel component. This paper presents a synthesis of available literature on concepts that have been or could be applied to develop these inputs. The paper also documents the painting decision trees and tables that have been developed in the literature and describes past methodologies that have been used to develop these decision support tools.